Values, Motives, and Organic Food Consumption in China: A Moderating Role of Perceived Uncertainty - Wei, Sheng; Liu, Furong; She, Shengxiang; Wu, Rong (Frontiers in Psychology, 2022)
The present research attempts to understand the importance of altruistic and egoistic value in determining the consumers’ motives and intention to purchase organic food. Using the face-to-face survey approach, a total of 1863 responses was collected from consumers in China. Data analysis was performed using two step structural equation modeling (SEM) approach, i.e. measurement model and structural model. Findings indicated that, both of the values influence the intention to purchase organic food through the mediation of motives. Specifically, altruistic value influences the environmental concern and egoistic value influences the health concern. Moreover, the perceived uncertainty negatively moderates the relationship between consumer health concern and organic purchase intention while positively moderates the relationship between consumer environmental concern and organic purchase intention. Several implications and suggestions are also discussed.